ANALISIS FEED BACK PADA WEBSITE ROOM MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Fira Mulia; Sudirman; Renny (STMIK KHARISMA Makassar, 2023)
Time efficiency and registration mechanisms are one of the challenges faced today. Website Room makes it easy to register for an event with easy access via the https://room-idn.com/ website page. To ensure the feasibility of the Website Room, an evaluation has been carried out through usability tests using the usability scale system method. This test analyzes the direct feedback given by the user to find out whether the user has understood the flow and how this application works. From user feedback, it can be analyzed related aspects that have been satisfactory, which need to be improved, improved and eliminated as well as to improve room features more quickly, easily, and accurately. From the results of the study, the resulting SUS score of 69.41 reflects the feasibility of the Room website as a website page with acceptability ranges at a marginally high level. Website Room has a user grade scale value for a category D website, and an Adjective Rating level for a website in the OK category. So overall, the website room is categorized as worthy to be released to the public.